1995
DOI: 10.1515/jpme.1995.23.5.353
|View full text |Cite
|
Sign up to set email alerts
|

Automated 24-hour ambulatory blood pressure monitoring in preeclampsia

Abstract: A prospective controlled study was designed to compare automated 24-hour ambulatory blood pressure monitoring with intermittent blood pressure recordings obtained using a sphymomanometer. Blood pressure was measured in 20 hospitalized preeclamptic women in the third trimester. Data obtained using the Spacelabs automated blood pressure monitor was recorded over a period of 24 hours, and thereafter stored and processed in a computer. During the same 24 hour period, blood pressure and heart rate were measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The Spacelabs 90207 ambulatory BP monitor was tested most often (N=10 articles). 28, 37, 39, 46, 52, 53, 58, 64-66 The majority of devices (N=23) examined used the oscillometric method, and the remainder of devices (N=5) used the auscultatory method. Of the 41 included articles, 31 used a standard validation protocol or a modification of one (Tables 1 to 3): 1 used the AAMI protocol, 27 used the BHS (7 used the 1990 version and 2 used a modification of it, and 18 utilized the 1993 version), 3 used the ESH-IP (2 used the 2002 version and 1 used the 2010 version).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spacelabs 90207 ambulatory BP monitor was tested most often (N=10 articles). 28, 37, 39, 46, 52, 53, 58, 64-66 The majority of devices (N=23) examined used the oscillometric method, and the remainder of devices (N=5) used the auscultatory method. Of the 41 included articles, 31 used a standard validation protocol or a modification of one (Tables 1 to 3): 1 used the AAMI protocol, 27 used the BHS (7 used the 1990 version and 2 used a modification of it, and 18 utilized the 1993 version), 3 used the ESH-IP (2 used the 2002 version and 1 used the 2010 version).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, although several studies tested the same device, we did not attempt to perform a meta-analysis due to the small number of studies in which these devices were validated without protocol violations. Lastly, for the 11 studies that followed a non-standard validation protocol 27, 28, 43, 48-52, 61 we were unable to adjudicate grades or assess violations and cannot comment on the validity of the devices examined. The majority of devices included in this review were oscillometric and utilize proprietary algorithms to calculate SBP and DBP.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of ABPM measurements to determine BP variability, diurnal variation, and HR variation may be diagnostically superior to the CSM in the evaluation of hypertension. 6,7 Nevertheless, the ABPM has not been adopted widely for use during pregnancy.…”
mentioning
confidence: 99%
“…Other sources of confusion include the use of automated blood pressure monitors, some of which underestimate the blood pressure in pre‐eclamptic women by a mean of 8 mmHg when compared with conventional sphygmomanometry 22 . Use of ambulatory devices has shown that mean blood pressure varies during the day by almost 5 mmHg 23 , and that clinic blood pressures are commonly higher than those in women at rest 24 . These variations can result in what has been called the ‘yo‐yo’ effect, where women are found to have a diastolic blood pressure exceeding 90 mmHg in the clinic and are admitted for observation.…”
mentioning
confidence: 99%